Pengaruh Penambahan Sabut Kelapa Terhadap Agregat Pada Kuat Tekan Beton K-175 - Siregar, Riska Febriana; Harsusani, Harsusani; Kamil, Firmanilah (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
The use of organic waste as a substitute material in concrete mixtures is one of the efforts to reduce environmental impacts and optimize the utilization of existing natural resources. Coconut fiber, as one of the abundant agricultural wastes, has the potential to be used as an aggregate substitute in concrete. This study aims to analyze the effect of coconut fiber addition on the compressive strength of K-175 grade concrete. Coconut fiber was used as a partial replacement for coarse aggregate with variations of 0%, 0.3%, 0.5%, and 0.8%. Concrete was tested at 7, 14, and 28 days to measure the compressive strength produced at each test age. The results showed that the control concrete (without coconut fiber) produced the highest compressive strength at all test ages. The addition of coir caused a decrease in compressive strength, especially at 7 days, which was due to the interaction between coir and cement matrix which was not optimal at the initial stage of hydration. However, at 28 days, the concrete with coir addition showed an increase in compressive strength although it was not significant compared to the control concrete. The optimum level of coir that does not significantly reduce the concrete quality is about 0.3%. Despite the reduction in compressive strength, the concrete produced at this level still meets the strength standards required for lightweight concrete applications or concrete with medium strength specifications. This study suggests that coir can be considered as an alternative aggregate replacement material in the production of environmentally friendly concrete, with appropriate proportion adjustments to optimize concrete performance. Keyword: aggregate, coconut fiber, concrete compressive strength, eco-friendly concrete, K-175 concrete.